MECHANISMS OF CARRYING OUT THE AUDIT OF EXPENSES OF MUNICIPAL UNITARY ENTERPRISES - Valerii N. Alferov (Модернизация, инновация, развитие, 2015)
Importence. In the article the study of the mechanisms of the audit costs of municipal unitary enterprises providing public utilities is conducted.Objectivs. The features of the audit of costs and factors have a significant impact on the functioning mechanism of the municipal unitary enterprise providing utility services Methods. Empirical research methods based on the examination ofents and results of the municipal unitary enterprise providing utility services.Results. It considers the problems to be solved in the course of the audit cost, the stages of the audit costs and factors that have a significant impact on the functioning mechanism of the municipal unitary enterprise.Conclusions and Relevance. The municipal unitary enterprises should always be audited, as they are not only an integral element of the Russian economy, but also acts as an intermediary between the municipality and the population as redistribute incomes by implementing its socially significant activities. The central role of the audit in this case is given to the study of characteristics of the constituent elements of the analytical accounting system of income and expenditure of municipal unitary enterprises.